MODEL OF CHARACTER DEVELOPMENT BASED ON THE FIVE PRECEPTS FOR SECONDARY STUDENTS UNDER THE JURISDICTION OF THE OFFICE OF THE PRIVATE EDUCATION COMMISSION - Chaisiri, Narinrat; Dhanapañño, Phramaha Sombat; Ruangsanka, Rawing (Journal of Educational Review Faculty of Education in MCU, 2021)
The objectives of this research article were 1) to study the state of problems of characteristics based on the 5 precepts of secondary school students, 2) to develop the model of character development based on the 5 precepts, and 3) to propose a model of character development based on the five precepts for secondary students under the Jurisdiction of the office of the private education commission. Mixed methods research was used for the design, and there were 3 steps of research method which were step 1 study the state of problems of characteristics based on the 5 precepts of secondary school students using 1) the questionnaires with 381 teachers, and data was analyzed by using statistics such as mean, percentage, and standard deviation, and 2) interview 5 key informants, and analyze the data with content analysis. Step 2 develop the model of character development based on the 5 precepts which were 1) develop the model by using focus group discussion of 12 experts, analyze the data by content analysis, and 2) validate the model with the evaluation form. The sample consisted of 286 school administrators who analyzed the data with statistics such as mean, percentage and standard deviation. Step 3 propose a model of character development based on the five precepts for secondary students under the Jurisdiction of the office of the private education commission. Results of the research revealed that 1) the state of problems of characteristics based on the 5 precepts of secondary school students in the overall level were at a high level. When considering each aspect, four aspects were shown at high level which were consciousness, right livelihood, benevolence, Kam Sangworn, and verbal truth was at a moderate level. 2) The development of the model of character development based on the 5 precepts is at a high level, and 3) a model of character development based on the five precepts for secondary students under the Jurisdiction of the office of the private education commission consisted of 4 parts, which were part 1 Introduction which were 1) Principles, 2) Objectives, 3) Context of educational institutions; Part 2 Model which were 1) 5 precepts, 2) characteristics according to 5 precepts, 3) process development of the characteristics according to the 5 precepts, 4) Project; Part 3 Implementation of the model which were 1) preparation, 2) implementation, 3) evaluation; and part 4 success conditions.